Vpogled v uravnavano eksocitozo - Flašker, Ajda (Medicinski razgledi, 2011)
Exocytosis, part of which is the merger of the vesicle and the plasma membrane, is characteristic for eukaryotic cells, which engage this process ina myriad of cell functions. For a long time it was believed that exocytosis was predominantly regulated by proteins, a view referred to as 'proteocentric'. Only recently it was shown that many oflipids, previously considered as passive cell membrane components, also play vital roles in regulation of exocytosis. Among others, such lipids are phosphatidylinositol-4,5-biphosphate, diacylglycerol, polyunsaturated fatty acids, sphingosine and cholesterol. Much like proteins, lipids act at various points in the process and influence exocytosis in various ways. The goal of this article is to highlight the role of lipids in exocytosis.
Keywords: Eksocitoza; Exocytosis; Membrana, zlitje; Membrane Fusion; Membrane Lipids; Fosfatidilinozitol 4,5-difosfat; Digliceridi; Phosphatidylinositol 4,5-Diphosphate; Membranski lipidi; Diglycerides; Fatty Acids, Unsaturated; Maščobne kisline nezasičene; Cholesterol; Holesterol; Membranske beljakovine; Sphingosine; Okulocerebrorenalni sindrom; Membrane Proteins; Botulism; Sfingozin; Oculocerebrorenal Syndrome; Botulizem; celice; Niemann-Pick Disease; celična membrana; fuzija; lipidi